Overview of Aga Genes and their Role in Utilization of N-Acetyl-D-Galactosamine and D-Galactosamine by Bacteria - Petruńko Leon; Gmiter Dawid (Postępy Mikrobiologii)
Bacteria use a variety of mechanisms in order to successfully survive in hosts. To support proliferation sophisticated means of maintenance in host especially metabolism of carbon and nitrogen is needed. One metabolic mechanism is the metabolism of amino sugars which are being used simultaneously as a carbon and nitrogen source. D-galactosamine (GalN) and N-acetyl-D-galactosamine (Gal-NAc) and their derivatives are widely used by bacteria. For instance, they build parts of cell wall and LPS. The metabolism of both amino sugars is performed and controlled by proteins encoded by aga genes, present in a wide variety of Proteobacteria. The genetic mechanism underlying this metabolic pathway is, however not yet fully known. Despite this, there is a possibility of using this pathway as a target for therapy, especially in the times of ever-growing danger of bacterial drug resistance. The goal of this article was to present the current knowledge of aga genes and their importance in GalN and GalNAc metabolism.